The results of applying the model of bachelor students’ key competences development by the means of e-learning at the university - Budenkova, Evgenia (Traektorii͡a︡ nauki : mezhdunarodnyĭ ėlektronnyĭ nauchnyĭ zhurnal, 2016)
The social and state order for training competent bachelors, capable of professional activities in various sociocultural contexts,  modern requirements for informatization of higher education actualize the problem of bachelor students’ key competences development by  means of e-learning at a university. However, the experts point out the insufficient conceptual development of the theoretical bases of bachelor students’ key competences evolvement by means of e-learning, which is increasingly coming into conflict with objective needs of university practice in evidence-based models of bachelor students’ key competences development. Therefore, the research objective is to develop the scientifically-based model of bachelor students’ key competences development by means of e-learning and to test the effectiveness of the model implementation in the course of experimental work at a university. The scientific and practical implications of the research consist in designing the pedagogical model of bachelor students’ key competences development by means of e-learning with the focus on implementing the pedagogical conditions in the university educational process. The research results indicate that the implementation of the designed model at the university contributes to effective development of some bachelor students’ key competences. Общественно-государственный заказ на подготовку компетентных бакалавров, способных к профессиональной деятельности в разнообразных социокультурных контекстах, и современные требования к информатизации высшего образования актуализируют проблему формирования общекультурных компетенций бакалавров средствами электронного обучения. Однако специалисты отмечают недостаточную концептуальную разработанность теоретических основ формирования общекультурных компетенций на базе электронного обучения, которая все чаще приходит в противоречие с объективными потребностями вузовской практики в научно-обоснованных моделях развития общекультурных компетенций. В данной связи целью исследования является разработка научно-обоснованной модели формирования общекультурных компетенций студентов-бакалавров средствами электронного обучения и проверка результативности внедрения модели в ходе опытно-экспериментальной работы в вузе. Научно-практическая значимость исследования заключается в создании педагогической модели формирования общекультурных компетенций студентов-бакалавров средствами электронного обучения с ориентацией на осуществление педагогических условий в образовательном процессе вуза. Результаты исследования свидетельствуют о том, что применение модели в вузе способствует результативному формированию ряда общекультурных компетенций студентов-бакалавров. Суспільно-державне замовлення на підготовку компетентних бакалаврів, здатних до професійної діяльності в різноманітних соціокультурних контекстах, і сучасні вимоги до інформатизації вищої освіти актуалізують проблему формування загальнокультурних компетенцій бакалаврів засобами електронного навчання. Проте фахівці відмічають недостатню концептуальну розробленість теоретичних основ формування загальнокультурних компетенцій на базі електронного навчання, яка все частіше приходить в протиріччя із об’єктивними потребами практики ВНЗ у науково-обгрунтованих моделях розвитку загальнокультурних компетенцій. У цьому зв'язку метою дослідження є розробка науково-обгрунтованої моделі формування загальнокультурних компетенцій студентів-бакалаврів засобами електронного навчання і перевірка результативності впровадження моделі у ході дослідно-експериментальної роботи у ВНЗ. Науково-практична значущість дослідження полягає у створенні педагогічної моделі формування загальнокультурних компетенцій студентів-бакалаврів засобами електронного навчання з орієнтацією на здійснення педагогічних умов в освітньому процесі ВНЗ. Результати дослідження свідчать про те, що застосування моделі у ВНЗ сприяє результативному формуванню ряду загальнокультурних компетенцій студентів-бакалаврів.